Occurrence of Guillain-Barre syndrome during the initial symptomatic phase of COVID-19 disease: coincidence or consequence? - Seixas, Rui (2021)
Viral infections are frequently present before the clinical manifestation of Guillain-Barre syndrome (GBS). Multiple studies on coronaviruses have shown that these viruses have neurotropic characteristics, and their molecular mimicry can induce inflammatory demyelinating neuropathy. Herein, we describe a case of a GBS in an 85-year-old patient infected with SARS-CoV-2, manifested with acute progressive symmetric ascending quadriparesis, urinary dysautonomia, and dysphagia, who responded well to treatment with intravenous human immunoglobulin.